Effects of repetitive peripheral magnetic stimulation on spasticity evaluated with modified Ashworth scale/Ashworth scale in patients with spastic paralysis: A systematic review and meta-analysis - Pan, Jia-Xin; Diao, Ying-Xiu; Peng, Hui-Yuan; Wang, Xi-Zhen; Liao, Lin-Rong; Wang, Mao-Yuan; Wen, You-Liang; Jia, Yan-Bing; Liu, Hao (Frontiers in Neurology, 2022)
Background Spasticity is a common motor disorder resulting from upper motor neuron lesions. It has a serious influence on an individual's motor function and daily activity. Repetitive peripheral magnetic stimulation (rPMS) is a non-invasive and painless approach developed for therapeutic intervention in clinical rehabilitation. However, the effectiveness of this intervention on spasticity in patients with spastic paralysis remains uncertain. Objective This study aimed to investigate the effectiveness of rPMS on spasticity, motor function, and activities of daily living in individuals with spastic paralysis. Methods PubMed, PEDro, Embase, Cochrane Library, and Web of Science were searched for eligible papers with date up to March 31, 2022. Two independent researchers conducted study screening, data extraction, and methodological quality assessment. RCTs that explored the effects of rPMS on spasticity, motor function, and activities of daily living in patients with spastic paralysis were included for review. The Cochrane collaboration tool was used to assess methodological quality. The cumulative effects of available data were processed for a meta-analysis using Reedman software. Results Eight studies with 297 participants were included. Most of the studies presented low to moderate risk of bias. Compared with the control group, the results showed that rPMS had a significant effect on spasticity (all spasticity outcomes: standardized mean difference [SMD] = −0.55, 95% confidence interval [CI]: −0.94 to −0.16, I2 = 40%, and P = 0.006, Modified Ashworth Scale: mean difference [MD] = −0.48, 95% CI: −0.82 to −0.14, I2 = 0%, and P = 0.006), motor function (Fugl–Meyer Assessment: MD = 4.17, 95% CI: 0.89 to 7.46, I2 = 28%, and P = 0.01), and activities of daily living (Barthel Index: MD = 5.12, 95% CI: 2.58 to 7.67, I2 = 0%, and P < 0.0001). No side effect was reported. Conclusion The meta-analysis demonstrated that the evidence supported rPMS in improving spasticity especially for passive muscle properties evaluated with Modified Ashworth Scale/Ashworth Scale, as well as motor function and daily activity of living in individuals with spastic paralysis. Study registration The reviewed protocol of this study is registered in the international prospective register of systematic reviews (PROSPERO) (CRD42022322395). Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#recordDetails, identifier CRD42022322395.